Product lines for digital information products - Pankratius, Victor (KIT Scientific Publishing, 2007)
Digital information products are an important class of widely used digital products, whose core benefit is the delivery of information or education (e.g., electronic books, online newspapers, e-learning courses).This book introduces a novel and systematic approach, Product Lines for Digital Information Products (PLANT), which focuses on the creation of variants of such products within a product line, and which extends concepts from the area of software product lines.